Keanekaragaman Jenis Anggang-anggang (Gerris marginatus) di Aliran Sungai Taman Wisata Alam Kerandangan Kabupaten Lombok Barat - Efendi, Rusnadi (Lembaga Pendidikan, Penelitian, dan Pengabdian Kamandanu, 2024)
Flywheels are a type of insect belonging to the Family Gerridae. Flywheels are insects that are usually found in calm waters such as ponds, rivers and lakes. The aim of this research was to determine the index of diversity of flywheels species in the river flow of Kerandangan Nature Tourism Park, West Lombok Regency. The type of research used is exploratory descriptive research. The data analysis technique in this research uses the Shannon-Wiener diversity index. The results of the research show that the species diversity index value of flywheels (Gerris marginatus) in the Kerandangan Nature Tourism Park is in the low category, with a total of 0.0693 in post 1, post 2 totaling 0.3518, and post 3 totaling 0.3463.